Allergenicity Assessment of Novel Food Proteins: What Should Be Improved?. Issue 1 (January 2021) - Fernandez, Antonio; Mills, E.N. Clare; Koning, Frits; Moreno, F. Javier
Abstract : Allergenicity prediction is one of the most challenging aspects in the safety assessment of foods derived from either biotechnology or novel food proteins. Here we present a bottom-up strategy that defines a priori the specific risk assessment (RA) needs based on a database appropriately built for such purposes.